Corporate Social Responsibility: A Very Short Introduction - Moon, Jeremy (New York Oxford University Press, 2014)
Corporate social responsibility has been defined as "the responsibility of enterprises for their impacts on society." Is Corporate Social Responsibility (CSR) just window dressing or is it a contradiction in terms? In this Very Short Introduction, Jeremy Moon shows that CSR holds much more value than it first appears, and examines how it has come of age in recent years. Illustrating the sorts of CSR investments companies make, the ways in which they practice CSR, and the challenges this brings, Moon considers how the principles migrated from their US roots to become a global business phenomenon. Exploring the place of CSR in different economic, social, political, and managerial contexts, this short guide considers the many positives, but also challenges, that CSR can present for companies, societies, and governments worldwide.
Includes Index and Illustrations.
Keywords: Social responsibility of business